Ventricular-Peritoneal Shunt in Newborns in a High-Risk Maternity Unit: Case Series - Barbosa, Amanda Ferreira; de Carvalho Neto, José Nolasco; Lyra, Carlos Alberto Miranda; Cavalcante, Tiago de Paiva; Morais, Rilton Marcus; Oliveira, Arthur Maynart Pereira (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2020)
Objective To identify factors related to ventricular-peritoneal shunt (VPS) complications in pediatric patients at a high-risk maternity hospital.Methods Prospective study, conducted between September/2018 and June/2019, with selected newborns without previous ventricular bypass who underwent neurosurgery for VPS placement in a high-risk maternity hospital in the state of Sergipe, Brazil. Diagnosis of hydrocephalus occurred by transfontanelle ultrasound. The variables were analyzed by Student t-test, adopting p < 0.05 as statistical significance.Results Seven newborns participated in the study, 3 male and 4 female. Folic acid supplementation during pregnancy was considered a positive influencing factor in the 1st minute Apgar. Hydrocephalus secondary to premature hemorrhage was present in most newborns. Prematurity, 1st minute Apgar score < 7, and birth weight < 2,500 g did not represent a significant negative risk factor for prolonged hospitalization after neurosurgery. One newborn had cerebrospinal fluid infection and was the only one with heart disease.Conclusion This is the first scientific research that associates the benefits of maternal use of folic acid during pregnancy to better newborn Apgar scores. Only one newborn developed complications after neurosurgery, the only one with an associated comorbidity. Further studies are needed to provide more evidence on risk factors related to complications of VPS implantation in newborns. This neurosurgical procedure in a high-risk maternity contributed to the early management of hydrocephalus.
Keywords: ventricular-peritoneal shunt; neurosurgery; pediatrics